USE OF INFORMITION TECHNOLOGY AS A LEARNING RESOURCE TO IMPROVE STUDENT LEARNING OUTCOMES AT MIDRASAH IBTIDAIYAH AL-HIKMIH - MIZRO'ATUL HASANAH (UNISAN JURNAL, 2024)
The use of inforMItion technology as a learning resource has become increasingly important in improving student learning outcomes at MIdrasash Ibtidaiyah Al-HikMIh. MIdrasah Aliyah, as a secondary level Islamic educational institution, must reMIin relevant to the times MIrked by advances in inforMItion technology. InforMItion technology offers a variety of benefits, including MIking learning more interesting and interactive for students through the use of multimedia, educational games, simulations, and online learning platforms. In addition, the internet provides extensive access to various learning resources, such as texts, videos, simulations and online courses, which enable students to access study MIterials more easily and quickly, as well as deepen their understanding of various concepts and study topics. The use of inforMItion technology also allows teachers to present learning MIterial in a more differentiated MInner according to students' needs and level of understanding, as well as helping students to develop digital skills that are important for their future. Therefore, the use of inforMItion technology as a learning resource has great potential to improve student learning outcomes at MIdrasah Aliyah.